Using the Scientific Method to Improve Game Bird Management and Research: Time - G. R. Potts (National Quail Symposium Proceedings, 2017)
Aware of the time lag that frequently exists between declines in biodiversity and effective conservation to correct and reverse the declines, I examine some reasons behind this problem. Experience with species as diver se as the shag (Phalacrocorax aristotelis) and grey partridge (Perdix perdix) shows the main problem to be the long period of time needed to detect problems, to define causation, to install effective change s in policy and, finally, to bring about restoration. The time needed to conduct research and implement policy to solve such problems often exceeds the time span of a career in ecology. Speedier results are therefore essential, but they will depend in part on removing the barriers between practitioners and theorists on the one hand and between practical applied ecologists and bureaucratic policy maker s on the other.